2013
DOI: 10.1111/jne.12040
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Receptor‐Bound Protein 10‐Mediated Negative Regulation of the Insulin‐Like Growth Factor‐1 Receptor‐Activated Signalling Pathway Results in Cognitive Disorder in Diabetic Rats

Abstract: Growth factor receptor-bound protein 10 (Grb10) is a Src homology 2 domain-containing protein and one of the binding partners for several transmembrane tyrosine kinase receptors, including insulin receptor (IR) and insulin-like growth factor-1 receptor (IGF1-R). The hippocampus, which is critical for cognitive functions, is one of the main distribution areas of Grb10 in the central nervous system. In recent years, diabetic encephalopathy has been defined as a third type of diabetes and the IGF1-IR pathway was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, delivery of insulin directly into hippocampus enhances learning and memory in rats, while blockade of endogenous hippocampal insulin markedly impairs spatial learning and memory (McNay and Recknagel, 2011). Several genes in the insulin pathway are known to be involved in learning and memory; such as the insulin receptor ( Insr) (Zhao et al, 2004), the insulin-like growth factor 2 ( Igf2) (Chen et al, 2011), the Igf2 receptor (Igf2r) (Chen et al, 2011, Lee et al, 2015) , the ras-guanine nucleotide releasing factor 1 ( Rasgrf1 ) (Fernandez-Medarde et al, 2007) and the growth factor receptor-bound protein 10 ( Grb10 ) (Ma et al, 2013). Interestingly, the pleomorphic adenoma gene-like 1 ( Plagl1/Zac1 ) gene regulates a gene network involving Igf2, Igf2r, Grb10 and Rasgrf1 (Varrault et al, 2006, Hoffmann and Spengler, 2012, Charalambous et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, delivery of insulin directly into hippocampus enhances learning and memory in rats, while blockade of endogenous hippocampal insulin markedly impairs spatial learning and memory (McNay and Recknagel, 2011). Several genes in the insulin pathway are known to be involved in learning and memory; such as the insulin receptor ( Insr) (Zhao et al, 2004), the insulin-like growth factor 2 ( Igf2) (Chen et al, 2011), the Igf2 receptor (Igf2r) (Chen et al, 2011, Lee et al, 2015) , the ras-guanine nucleotide releasing factor 1 ( Rasgrf1 ) (Fernandez-Medarde et al, 2007) and the growth factor receptor-bound protein 10 ( Grb10 ) (Ma et al, 2013). Interestingly, the pleomorphic adenoma gene-like 1 ( Plagl1/Zac1 ) gene regulates a gene network involving Igf2, Igf2r, Grb10 and Rasgrf1 (Varrault et al, 2006, Hoffmann and Spengler, 2012, Charalambous et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Grb10 plays a key role in the function of vascular smooth muscle cells by regulating the proliferation, migration, and inflammatory gene expression of these cells [30]. Another study reported that the expression of GRB10 in the hippocampus of diabetic rats is increased, impairing neural function and cognition by negatively regulating the insulin-like growth factor-1 receptor signaling pathway [31]. Moreover, the expression of insulin-like growth factor-1 is related to the proliferation, differentiation, and matrix synthesis of chondrocytes, which are essential in cartilage morphogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that endogenous GRB10 expression was increased in the hippocampus of rats with diabetic encephalopathy and that this increase might result in damaged nerve functions and cognitive impairments. In addition, the insulin/IGF1 signaling pathways have been implicated in dysregulated synaptic maturation and may play key roles in brain aging and dementia as well as learning and cognitive functions in rodent models [ 14 , 19 ]. In the present study, the IGF1 and IGFBP3 levels in the patient were far below normal levels, consistent with a model in which the duplication of GRB10 directly inhibits the phosphorylation of the IGF1R substrate and reduces the level of Grb10 expression to below normal limits, which may result in nervous system impairments such as growth delays and intellectual disabilities (ID) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%